Rancang Sistem Pendukung Keputusan Untuk Kelayakan Penerima Bantuan Sosial Tunai (BST) Pada Masyarakat Miskin Berbasis Website Menggunakan Metode Fuzzy (Studi Kasus : Desa Sukanagara Kecamatan Cikupa) - Asep Suryana; Indra Cahya Firdaus (CV. Multi Kreasi Media, 2023)
In the era of the corona virus or covid-19 pandemic in Indonesia, the socio-economic impact of the COVID-19 pandemic has had a major impact on the welfare of the community. Therefore, the government is trying to overcome the economic problems of the people affected by the pandemic by providing social assistance, especially for the poor or the poor. less fortunate. However, there are problems that occur in Sukanagara village in the distribution of social assistance that is not right on target due to the absence of a tool or system that assists officers in selecting candidates for social assistance recipients from the government. To overcome these problems, it is necessary to have a decision support system for the selection of prospective recipients of social assistance using the fuzzy method by applying criteria data from income, number of dependents and floor area in house buildings. With a decision support system and applying a fuzzy method in the form of a website, it will make it easier for social service officers or village officials to determine which residents deserve social assistance.